Estimating Returns to Agricultural Research, Extension, and Teaching at the State Level - Norton, George W.; Coffey, J. D.; Frye, E. B. (Cambridge University Press, 1983)
The majority of decisions concerning investment and allocation of public funds for agricultural research, extension, and teaching (RET) are made at the state-level, while most of the quantitative RET evaluations are made on a national basis. This paper illustrates an approach for conducting a disaggregated state-level evaluation of agricultural research, extension, and teaching. Ridge regression is employed to handle multicollinearity problems.